Evaluation of microtoxicity and biodegradability of residual organic solvents in pharmaceutical wastewater by combined prediction-test system. Issue 58 (13th December 2016) - Zhao, Zhongqing; Cheng, Siyuan; Qin, Zhe; Ma, Ke; Jin, Xiaoling; Liang, Shu-xuan
Abstract: The wastewater generated in pharmaceutical process generally contains residual organic solvents (ROSs) which will cause the toxicity and inhibition of the micro-organisms in treating wastewater, thus affecting the treatment effect of wastewater. The aim of this study was to establish a system for the analysis and evaluation of microtoxicity and biodegradability of ROSs in pharmaceutical wastewater. The quantitative structure activity relationship models were used to predict the toxicity and biodegradability; meanwhile, the biological toxicity was tested by the method of dehydrogenase activity (DHA) as well as luminescent bacteria and biodegradability was measured by shaking experiment. The proposed system was applied to predict and evaluate toxicity and biodegradability of toluene, acetone, isopropanol and dichloromethane in pharmaceutical wastewater. The results showed that the actual measured values fitted well with the calculated values. The microtoxicity of toluene was the highest and the degradation was more difficult. Dichloromethane toxicity was the second highest after toluene and more easily degradable. Acetone and isopropanol were less toxic and had easy degradation. The fact indicated the system was reliable and easy to operate which could be extended to the screening and identification of highly toxic and difficult degradation components in industrial wastewater.